Factors Associated with Poly Drug Use in Adolescents - Jongenelis, Michelle; Pettigrew, S.; Lawrence, D.; Rikkers, W. (Springer, 2019)
Poly drug use in adolescents represents a significant public health issue, heightening risk for abuse, dependency, and a variety of short- and long-term psychological, psychosocial, and health consequences. However, past studies have typically examined just one or two substances in isolation and there is a lack of research that has comprehensively examined possible predictors of poly drug use in adolescents. To inform the development of comprehensive prevention programs that can simultaneously target multiple substances, the present study sought to identify psychological, environmental, and demographic factors that are most strongly associated with alcohol, tobacco, and cannabis poly drug use. Adolescents aged 15 to 17 years (n = 1661; 50.9% male) completed a survey on their use of alcohol, tobacco, and cannabis over the last 30 days. Various psychological, environmental, and demographic factors were also assessed. Weighted multiple-level logistic regression was conducted to assess the factors associated with poly drug use. In total, 20.3% of respondents had used at least one substance, 6.7% reported using two substances, and 3.3% reported using all three substances. The most common combined pattern of use was alcohol and tobacco, followed by alcohol and cannabis. Several factors emerged as significant, with conduct problems, depression, and the school environment accounting for the most variance. Specific psychological and environmental factors appear to be particularly important domains to target in adolescent substance use prevention programs. Early identification of adolescent depression and conduct problems and the development of programs that address these symptoms in youth may be effective approaches to delaying or preventing poly drug use in this population.